2019
DOI: 10.1002/chem.201902082
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Metal‐Free Formal Decarbonylation of α‐Branched Aliphatic Aldehydes at Ambient Temperature

Abstract: A sequence of a Baeyer–Villiger oxidation and a Lewis acid‐promoted reduction of the resulting formate with Et3SiH enabled the metal‐free formal decarbonylation of tertiary and secondary aliphatic aldehydes. The new methodology mimics the biosynthetic decarbonylation pathway through oxidative C−C bond cleavage rather than the C(O)−H bond activation known from conventional Tsuji–Wilkinson‐type reactions. The substrate scope is complementary to existing transition‐metal‐catalyzed protocols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…In analogy to the widely applied Barton‐McCombie reaction, [8] we planned to modify the hydroxy group in the first step to alter the selectivity in the subsequent B(C 6 F 5 ) 3 ‐catalyzed reduction. We anticipated the aforementioned change in mechanism from S N 2 to S N 1 for this reduction with hydrosilanes based on our previous study on the deoxygenation of benzylic formates in the context of a formal decarbonylation strategy [9] …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In analogy to the widely applied Barton‐McCombie reaction, [8] we planned to modify the hydroxy group in the first step to alter the selectivity in the subsequent B(C 6 F 5 ) 3 ‐catalyzed reduction. We anticipated the aforementioned change in mechanism from S N 2 to S N 1 for this reduction with hydrosilanes based on our previous study on the deoxygenation of benzylic formates in the context of a formal decarbonylation strategy [9] …”
Section: Methodsmentioning
confidence: 99%
“…Et 3 SiOMe ( 11 ) is ultimately reduced to methane ( 12 ) along with the corresponding disiloxane [12] . The deoxygenation of the secondary formate 6 a follows an S N 1 mechanism [9] . Silylcarboxonium ion 9 a dissociates into the benzylic carbenium ion 14 a and the silylated formate 13 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A formal decarbonylation of aliphatic aldehydes 29a-d via a sequence of Baeyer-Villiger oxidation and B(C 6 F 5 ) 3 -or BF 3 -$OEt 2 -catalysed deoxygenation of the resulting formate with Et 3 SiH as the reductant was developed by Richter and Oestreich (Scheme 27). 56 Mechanistic investigations suggested that an S N 1 mechanism is involved for the deoxygenation process.…”
Section: Boron Lewis Acids-catalysed Decarbonylationmentioning
confidence: 99%